The concept of sustainable residential college: a study on the provision of facilities in the public university residential colleges in Malaysia - Buyung, Mohd Reduan; Shafii, Haryati; Yusoff, Noor Ain; Buyung, Nurul Rewahidayu (Human Resource Management Academic Research Society, 2018)
This study was conducted to assist the development of a sustainable residential college in the future. Sustainable residential college is able to provide comfortable, conducive and complete amenities and facilities. The purpose of this study is to identify the level of comfort of the accommodation and the level of facilities in the Malaysian public university residential college. The methodology used was through a questionnaire on 2874 respondents at seven public university residential colleges. The questionnaire consists of three parts, namely part A related to demographics, part B relating to comfort in the accommodation and part C related to the provision of support facilities. Descriptive and inferential data analysis is used for quantitative data using the Statistical Package for the Social Sciences software. The results showed that the comfort of the respondents on the provision of accommodation was at a comfortable level. The correlation test showed that there was a weak positive correlation between the years of occupation and the duration of residential college with the comfort of the room. For the provision of support facilities, the facilities provided are still incomplete and do not meet the academic requirements or for the self-development of the residents. Overall, this study has contributed to discussions regarding the provision of facilities at sustainable residential colleges in turn leading to improved living quality of residents.